Production of polymeric membrane for natural gas separation - Ibrahim, Nor Azowa; Moradihamedani, Pourya; Yusof, Nor Azah (2014)
A method for preparing a composite membrane for gas purification includes the steps of forming a membrane from a polymer as a support layer by contacting and incorporating the polymer in a solvent, and fabricating a polysaccharide as a surface layer on the support layer. Particularly, the polymer is a thermoplastic polymer and the polysaccharide is a linear polysaccharide. Moreover, the step of the gas purification includes separating carbon dioxide from methane.